Alfabetização e alfabetizadoras: objeto inconsistente, ofício contingente - Niches, Cláudia Cardoso (Universidade do Vale do Rio dos Sinos, 2014)
The present paper aims at analyzing the weakness that involves the object of studies Literacy in the formative processes of Elementary School teachers. It has been set, in a more precise way, on how Literacy has been configured in the beginning of Elementary School teacher’s formation and how this is correlated to the job of teaching how to read and write. In order to develop the research, one found support in the wide theoretical field of the history of schooling in the West, pointing out the elements that structure the emergency of compulsory school in Brazil, as well, the place of Literacy and the formation of teachers as a whole. The analytical corpus includes Literacy teachers’ narratives, who have worked, for more than five years, in the first two years of Elementary public schools, in the city of Montenegro, Rio Grande do Sul. The methodological approach applied for the development of the empirical corpus made use of oriented narrative interview about: the meanings that the object Literacy and the fact of been literate takes on to those teachers, making references and/or identifications between those professionals; the epistemological dominant basis that support these teachers’ practical and instrumental knowledge, outlining their professional place; the implications of their formative processes in their im/possibilities as literacy teachers and, the elements that have been provoking tension in the cultural experience of Literacy, adjusting and projecting it. The analysis of the content was based in the Foucauldian discourse analysis that concerns to the meanings that the subjects attribute to the objects that surround them and their experiences, prioritizes descriptive proceedings, welcomes subjective interference and understands knowledge as a continuing and occasional production of true. The results of the research point to: 1) the inconsistency of Literacy in the formation of teachers, shaped by the predominance of the mechanical approach in the learning/ teaching reading and writing process, which does not prioritize the reading of the world; 2) the fragile introduction of Literacy concepts in this discourse that do not contemplate, the least, the huge role that literacy currently has; and 3) the fading of specific references related to literacy, offered by the multi discipline in sciences that contemplate this object. The inconsistency of Literacy ends up for being suppressed, in this discourse, by elements related to teaching job in its broader generic way. One can infer that the literacy job acquires a vulnerable status, as its object is invisible, not only in its formation but also in its schooling practice, supporting itself, therefore, in the predominance of knowledge and beliefs coming from the experiences of these professionals and over the fading of references connected to its specificities.
Keywords: Alfabetização; Formação de professores; Cursos de pedagogia; Ofício de alfabetizar; Literacy; Teachers formation; Pedagogy courses; Literacy job; ACCNPQ::Ciências Humanas::Educação